2021
DOI: 10.24115/s2446-62202021731255p.42-54
|View full text |Cite
|
Sign up to set email alerts
|

The professional choreographic education: current state and development trends

Abstract: The aim of the article is to highlight the features of the development of choreographic education at the beginning of the XXI century on the example of educational institutions of Great Britain and the United States, which train students in "Choreography" specialties. Methods: analysis, synthesis, induction, deduction, observation, description, tabular and graphical representation, comparison, systematization, questionnaire survey, hypothesis, abstraction and generalization. It was established that the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Many studies have shown that the dance education development at the beginning of the 21st century is characterized by the growth of students who wish to relate their lives to dance (Bigus et al, 2021;Wahyuni & Widyaningsih, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the dance education development at the beginning of the 21st century is characterized by the growth of students who wish to relate their lives to dance (Bigus et al, 2021;Wahyuni & Widyaningsih, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the modern view of the creative process, many degree theses used elements of drama, which gives their performances a modern sound(Eren & Öztug, 2020;Tleubay et al, 2020;Kozyntseva, Synakh & Dulebova, 2021).The issues of the global choreographic culture are becoming especially important at the present stage in the context of complex globalization. Currently, the choreographic culture, considered in the context of the entire artistic culture as an integral part of society's spiritual culture, is undergoing significant changes due to the complex globalization processes of cultural interpenetration and commercialization of all spheres of public life(Habe, Biasutti & Kajtna, 2021;Briot & Pachet, 2020;Wang, 2021;Bigus, Bilash, Vyshotravka & Khotsianovska, 2021).Following the trends in the educational process development in HEIs of artistic focus, let us consider the requirements for the musical competence of a future choreography teacher within the existing education system. Nowadays, future choreography teachers should know dance music's history, different countries' musical instruments, and composers' works.…”
mentioning
confidence: 99%